ENHANCING EFFICIENCY OF IRRIGATION SYSTEMS THROUGH COMBINATION OF IRRIGATION METHODS - Mohamed Eltayib, Muhanad Elshafie (Universiti Teknologi PETRONAS, 2018)
The sector that play an important role in reducing food scarcity is agriculture sector. Higher yields of crop productions hinge on the atmospheric condition of the location and the soil condition. However, countries like those in Africa hot climate condition will face difficulty in agriculture improvement for certain crops due to global warming. Excessive use of water in irrigating the crops will leads to ineffectiveness of irrigation systems. This create water scarcity that will bring huge impact on the production of crops and profitability of farm. Proper irrigation method need to be addressed in solving the efficiency usage of water to the crops. Thus, this research is focusing on enhancing efficiency of the irrigation systems through combining two irrigation methods. Three different irrigation method experiments were being tested.